2016
DOI: 10.1007/s10853-016-0134-y
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired durable superhydrophobic materials with antiwear property fabricated from quartz sands and organosilane

Abstract: In this study, we present a strategy to fabricate durable superhydrophobic materials by employing organosilane surface-functionalized quartz sand particles. The quartz sand particles are bonded intimately with diethoxydimethylsilane and triethoxymethylsilane to enhance the mechanical properties of the materials. The obtained materials possess superhydrophobicity with the water contact angle of 158 ± 1°and self-cleaning ability. Moreover, the materials can endure the 6H pencil hardness test and also can keep st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…25 For many reported superhydrophobic surfaces, slight attrition could destroy the superhydrophobicity, and some of them could not even withstand finger touching. 31,45,46 In this paper, the aluminum plates are etched by immersing in a hydrochloric acid, resulting in the formation of a microtextured surface composed of irregular, stairlike protrusions. The etched plates then were dip-coated with SiO 2 to generate a micronanoscale rough structure.…”
Section: Introductionmentioning
confidence: 99%
“…25 For many reported superhydrophobic surfaces, slight attrition could destroy the superhydrophobicity, and some of them could not even withstand finger touching. 31,45,46 In this paper, the aluminum plates are etched by immersing in a hydrochloric acid, resulting in the formation of a microtextured surface composed of irregular, stairlike protrusions. The etched plates then were dip-coated with SiO 2 to generate a micronanoscale rough structure.…”
Section: Introductionmentioning
confidence: 99%
“…So there are two kinds of methods to fabricate superhydrophobic surfaces. The one is to make micro-nano hierarchical surfaces modified subsequently with low surface energy materials, and the other one is to build a micro-nano roughness with low surface energy materials directly 14 . Considerable efforts have been devoted to preparing superhydrophobic materials for various purposes.…”
Section: Introductionmentioning
confidence: 99%
“…Qu et al . employed organosilane surface-functionalized quarts sand particles to fabricate durable superhydrophobic materials 14 . Among the quarts sand particles, covalent bonds were formed with the help of condensation by hydroxyl groups.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the formation of oxides the coefficient of friction and wear resistance get significantly low [62]. With the help of polymerization and condensation and using coating material as quartz sad particles and organosilane on glass and cardboard researcher get a 158-degree contact angle and this coating has very good wear resistance properties [63]. Wear resistance study of superhydrophobic coating made of hydrophobic silica nanoparticles and acrylic resin matrix on a glass substrate or polished iron tin plate has done by Li et al, They found that when the coating was abraded with same roughness abrasive paper as that of superhydrophobic layer than it decays faster than if it abraded by more roughened abrasive paper and durability of hydrophobicity will be maintained [64].…”
Section: Wear Resistancementioning
confidence: 99%